Optimization of nutritional and non-nutritional factors involved for production of antimicrobial compounds from Lactobacillus pentosus SJ65 using response surface methodology - Saraniya,Appukuttan (2014)
Bacteriocins from lactic acid bacteria are ribosomal synthesized antibacterial proteins/ peptides having wide range of applications. Lactobacillus pentosus SJ65, isolated from fermented Uttapam batter (used to prepare south Indian pan cake), produces bacteriocin having a broad spectrum of activity against pathogens. Optimization studies are of utmost important to understand the source of utilization and the conditions to enhance the production of metabolites. In the present study, an attempt was made to identify the parameters involved for maximal production of antimicrobial compounds especially bacteriocin from the isolate L. pentosus SJ65. Initially, optimal conditions, such as incubation period, pH, and temperature were evaluated. Initial screening was done using methodology onevariable-at-a-time (OVAT) for various carbon and nitrogen sources. Further evaluation was carried out statistically using Plackett-Burman design and the variables were analyzed using response surface methodology using central composite design. The optimum media using tryptone or soy peptone, yeast extract, glucose, triammonium citrate, MnSO4, dipotassium hydrogen phosphate and tween 80 produced maximum bacteriocin activity.